Integrative transcriptome and proteome revealed high-yielding mechanisms of epsilon-poly-L-lysine by Streptomyces albulus - Wang, Liang; Yang, Hao; Wu, Mengping; Zhang, Jianhua; Zhang, Hongjian; Mao, Zhonggui; Chen, Xusheng (Frontiers in Microbiology, 2023)
Introduction ε-poly-L-lysine (ε-PL) is a high value, widely used natural antimicrobial peptide additive for foods and cosmetic products that is mainly produced by Streptomyces albulus. In previous work, we developed the high-yield industrial strain S. albulus WG-608 through successive rounds of engineering. Methods Here, we use integrated physiological, transcriptomic, and proteomics association analysis to resolve the complex mechanisms underlying high ε-PL production by comparing WG-608 with the progenitor strain M-Z18. Results Our results show that key genes in the glycolysis, pentose phosphate pathway, glyoxylate pathway, oxidative phosphorylation, and L-lysine biosynthesis pathways are differentially upregulated in WG-608, while genes in the biosynthetic pathways for fatty acids, various branched amino acids, and secondary metabolite by-products are downregulated. This regulatory pattern results in the introduction of more carbon atoms into L-lysine biosynthesis and ε-PL production. In addition, significant changes in the regulation of DNA replication, transcription, and translation, two component systems, and quorum sensing may facilitate the adaptability to environmental pressure and the biosynthesis of ε-PL. Overexpression of ppk gene and addition of polyP6 further enhanced the ε-PL production. Discussion This study enables comprehensive understanding of the biosynthetic mechanisms of ε-PL in S. albulus WG-608, while providing some genetic modification and fermentation strategies to further improve the ε-PL production.